Christianity in Modern China: The Making of the First Native Protestant Church - Cheung, David (Studies in Christian Mission Ser., 2003)
This monograph studies a significant episode in Chinese Christianity. Focusing on the origins of Protestantism in South Fujian, it investigates the evolution of the churches which pioneered in indigenization and ecclesiastical union in China during the 19th century.